The influence of digitalization on foreign language academic and business communication in the global economy - Chyzh, Yuliia; Mokhniuk, Anna (Державний університет інформаційно-комунікаційних технологій, 2025)
Digitalization has significantly impacted academic and business communication in foreign languages in a globalized economy. It has opened up new opportunities for more effective language learning, intercultural communication, and professional interaction through technologies such as artificial intelligence, machine translation, video conferencing, and mobile applications. In business, digital tools help optimize communications, reduce costs, and expand companies' global presence.
Keywords: Digitalization; communication; machine translation; video conferencing and AI-powered tools